Working of Bamboo in Flowered Areas of Kundam Project of Madhya Pradesh State Forest Development Corporation - Hakeem, K. L. (Indian Forester, 1985)
Although the flowering in Kundam Project Division of M P.S.F.D C had occurred in 1971-73’ the regeneration of bamboo remained suppressed due to biotic influence and thick ground cover Bamboo is a strong light demander than is commonly opined. Selective operations were carrird’ to lift the canopy and to remove the ground cover. The regeneration was adopted at 4 m Ã— 4 m spacing. Soil working and weedlings were carried out. The results of growth in the very first growing season were fabulous.